VD_FINDINFO Décision / 2012 / 364 vom 4. Juni 2008 - VD Tribunal cantonal (2008)
DROIT D'OBTENIR UNE DÉCISION, RETARD INJUSTIFIÉ, PRINCIPE DE LA CÉLÉRITÉ | 29 al. 1 Cst., 26 al. 1 let. a LEP, 38 LEP, 393 al. 2 let. a CPP (CH), 396 CPP (CH)